The Effect of Interactive Multimedia Based on PowerPoint on the Learning Outcomes of Vocational High School Students - Neng Wilda; Tatu Munawaroh; Ari Fajria Novari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The use of engaging and interactive learning media is essential in the learning process at vocational high schools, particularly in accounting classes, which are often considered difficult and boring. One alternative that can be used is interactive multimedia based on PowerPoint, which can present material through text, images, animations, and quizzes, making it easier for students to understand. This study focuses on analyzing the impact of interactive multimedia based on PowerPoint on the learning outcomes of students at Rina Hasanah Vocational High School majoring in Accounting and Financial Institutions. The research method used is a true experiment with a Pre-test Post-test Control Group Design. The research population consisted of all 60 students in the 10th grade, divided into two groups: 30 students in the experimental group and 30 students in the control group, selected using simple random sampling. The research instrument consisted of a multiple-choice learning achievement test with 30 questions that had been tested for validity (22 valid questions) and reliability (α = 0.852). Data analysis was conducted using normality tests, homogeneity tests, independent t-tests, and N-Gain calculations. The results showed that the average post-test score of the experimental group (82.5) was higher than that of the control group (72.1). The t-test produced a calculated t-value of 4.215 > t-table 2.001 with a significance of 0.000 < 0.05, indicating a significant difference between the two groups. The N-Gain calculation also shows an increase in learning outcomes for the experimental group of 0.57 (moderate category), while the control group only increased by 0.31 (low category). It can be concluded that interactive multimedia based on PowerPoint is effective in improving students' learning outcomes in vocational high schools for the subject of Accounting, making it worthy of use as one of the innovative teaching strategies in vocational high schools.